Orientador pedagógico iniciante: inserção profissional e saberes necessários à atuação - Lourenço, Daniela de Ávila Pereira (Universidade Federal de São Carlos, 2020)
The objective of this research is to understand the process of professional insertion and knowledge necessary to perform of the pedagogical advisor at the beginning of his career. Because of that we carried out the Curricular Activity of Integration: Teaching, Research and Extension (ACIEPE) “Beginning pedagogical advisor - challenges, possibilities and necessary knowledge to perform'', through a partnership between the Federal University of São Carlos / Sorocaba and the prefecture of Sorocaba. We used the theoretical contribution of pedagogical advisor (ALMEIDA, 2006; PLACCO, ALMEIDA, SOUZA 2011; 2012; 2015; PLACCO, 2014), and the beginning of his career (HUBERMAN, 1989; MARCELO GARCIA, 2009, 2010). This type of training-research was aimed at pedagogical advisors at the beginning of their careers, and composed professionals from the prefectures of Cabreúva, Sorocaba and Votorantim. The research is qualitative and interpretative, the data were constructed from the selection of narrative writings of the pedagogical advisors, interaction and communication at the ACIEPE meetings, and from the legislation that regulates the pedagogical guidance in the three prefectures. We opted for data triangulation to analyze and interpret data because of the complexity, depth and diversity that presented themselves. The analyzes were carried out in two chapters: professional insertion, and necessary knowledge for perform. For each analytical chapter, we did the following movement: For each analytical chapter, we performed the following movement: the narrative writings were analyzed individually and, then, we performed the intersection of the information to find the categories of analysis; the legislation that standardizes the pedagogical guidance in the three municipalities was analyzed through documentary analysis, considering the studies of Cellard (2008), and at the end we performed the crossing of information between the three analyzed legislations to find information that directly impacted the insertion process professional, and in the construction of the knowledge necessary for perform; the interaction and communication during the ACIEPE meetings were analyzed through thematic episodes, adapted from Moura (1992), and at the end of each episode, we talked about the knowledge and experiences that the professionals told us about the process of professional insertion, and the knowledge that enables the performance of the pedagogical advisor at the beginning of his career. The closing of each analytical chapter brings the results found from the intersection of the partial results of the analysis with each of the selected instruments. The results of the research show that the type of employment relationship, the lack of knowledge of the job and the lack of specific training that line up with the characteristics of the beginning of the career and the specificity of the pedagogical orientation are factors that interfere in the professional insertion and in the perform of the pedagogical advisor in early career. To overcome the challenges faced, the beginning pedagogical advisor mobilizes experiential knowledge in the interpersonal, political, technical and scientific dimensions and of teaching, experience and self-knowledge. The relevance of implementing professional insertion and specific training programs was verified for the performance of pedagogical guidance. The relevance of implementing professional insertion and specific training programs was verified for the perform of the pedagogical orientation.
Beginning pedagogical advisor: professional insertion and knowledge necessary for performance
Keywords: Orientador pedagógico.; Inserção profissional.; Formação de professores.; Pedagogical advisor.; Professional insertion.; Teacher training.; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO